Factors influencing Indonesian organic certification rice consumption (case study of PT. Berkah Dua Agri and Agriwira Mandiri Sejahtera) - Meutiashifa, Nanda Izwin; Antriyandarti, Ernoiz; Nurhidayati, Indah (Agriekonomika, 2024)
Organic rice is rice that has the benefit of being a high source of carbohydrates and having health benefits, being fluffier and delicious to eat. Organic certification for agricultural products has a very important meaning in gaining consumer trust. The aim of this research is to analyze the factors that influence the consumption of organic rice with Indonesian Organic certification and analyze which factors have the most dominant influence on the consumption of organic rice with Indonesian Organic certification. The basic method is quantitative descriptive with purposive location determination with a total of 60 respondents. The location of this research was carried out at PT Berkah Dua Agri and Agriwira Mandiri Sejahtera. This location was determined because the research location provides organic rice with Indonesian Organic certification and has direct access to consumers who will be used as samples.  The data analysis method uses multiple linear regression analysis. The research results show that the price of organic rice, number of family members and tastes have a negative influence on the consumption of organic rice with Indonesian organic certification. The price of complementary goods and the price of substitute goods have a positive influence. The income variable has no effect. The most dominant factors are the prices of complementary goods and the prices of substitute goods